Wage Subsidy and Labor Market Flexibility in South Africa - Go, Delfin S.; Kearney, Marna; Korman, Vijdan; Robinson, Sherman; Thierfelder, Karen (2012)
In this paper, the authors use a highly disaggregate general equilibrium model to analyze the feasibility of a wage subsidy to unskilled workers in South Africa, isolating and estimating its potential employment effects and fiscal cost. They capture the structural characteristics of the labor market with several labor categories and substitution possibilities, linking the economy-wide results on relative prices, wages, and employment to a micro-simulation model with occupational choice probabilities in order to investigate the poverty and distributional consequences of the policy. The impact of a wage subsidy on employment, poverty, and inequality in South Africa depends greatly on the elasticities of substitution of factors of production, being very minimal if unskilled and skilled labor are complements in production. The desired results are attainable only if there is sufficient flexibility in the labor market. Although the impact in a low case scenario can be improved by supporting policies that relax the skill constraint and increase the production capacity of the economy especially towards labor-intensive sectors, the gains from a wage subsidy are still modest if the labor market remains very rigid.